ANALISIS TUTURAN DALAM PROSES JUAL BELI DILIHAT DARI SEGI TINDAK TUTUR DAN PERISTIWA TUTUR DI SEBUAH TOKO - Nenden Nurpratiwi Parliani; Isdayanti Isdayanti; Aditya Permana (IKIP Siliwangi, 2019)
This research is based on the research curiosity about speech acts and speech events that occur in interactions with traders and buyers in vegetable shops. From the background of the research, a problem statement can be drawn, namely how do speech acts and speech events occur at the interaction of traders and buyers at the vegetable shop? This study intends to find out the speech acts and speech events that occur in the interaction of traders and buyers in the vegetable shop. The method used is a qualitative descriptive method with the object of the research is the interaction of vegetable traders and buyers in a shop near residential areas of residents. The subjects of this study are speech acts and speech events that occur in the interaction of traders and buyers. The results of this study show conclusions, namely the variety of uses of language variations in the form of speech acts and speech events conducted by traders and buyers when interacting.